2021
DOI: 10.1002/pros.24131
|View full text |Cite
|
Sign up to set email alerts
|

M2a macrophage can rescue proliferation and gene expression of benign prostate hyperplasia epithelial and stroma cells from insulin‐like growth factor 1 knockdown

Abstract: Background Benign prostatic hyperplasia (BPH) is a common disease in elderly men and is often accompanied by chronic inflammation. Macrophages (several subtypes) are the main inflammatory cells that infiltrate the hyperplastic prostate and are found to secrete cytokines and growth factors. The current study aims to explore the effect of M2a macrophages on the development of BPH via insulin‐like growth factor 1 (IGF‐1). Methods Human prostate tissues, prostate, and monocyte cell lines (WPMY‐1, BPH‐1, and THP‐1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…The results showed that M2a macrophages expressed more IGF-1 than other subtypes ( 29 ) ( Figure 1 ). Knockdown of IGF-1 in WPMY-1 and BPH-1 cells attenuated cell proliferation, promoted cell apoptosis, retarded the cell cycle at the G0/G1 phase, and suppressed the EMT process in BPH-1 cells as well as the fibrotic process in WPMY-1 cells, which was reversible when cocultured with M2a macrophages ( 29 ). These data demonstrated that knockdown of IGF-1 expression in cultured BPH epithelial and stromal cells reduces proliferation and increases apoptosis.…”
Section: The Role Of Inflammation In Bphmentioning
confidence: 96%
See 2 more Smart Citations
“…The results showed that M2a macrophages expressed more IGF-1 than other subtypes ( 29 ) ( Figure 1 ). Knockdown of IGF-1 in WPMY-1 and BPH-1 cells attenuated cell proliferation, promoted cell apoptosis, retarded the cell cycle at the G0/G1 phase, and suppressed the EMT process in BPH-1 cells as well as the fibrotic process in WPMY-1 cells, which was reversible when cocultured with M2a macrophages ( 29 ). These data demonstrated that knockdown of IGF-1 expression in cultured BPH epithelial and stromal cells reduces proliferation and increases apoptosis.…”
Section: The Role Of Inflammation In Bphmentioning
confidence: 96%
“…These data demonstrated that knockdown of IGF-1 expression in cultured BPH epithelial and stromal cells reduces proliferation and increases apoptosis. These effects are reversed by coculture with M2a macrophages ( 29 ). This indicates the direction for the precise treatment of BPH in the future ( Figure 1 ).…”
Section: The Role Of Inflammation In Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…How IGF-1 signaling affects adrenal and testes function remains unknown ( 32 ). The role of IGF-1 signaling in prostate development and normal prostate physiology has not been established in vivo , however, silencing IGF-1 in not only the WPMY-1 prostate stroma cell line, and but also BPH-1, a prostate epithelium cell line, decreased cell proliferation and increased apoptosis rate in vitro ( 33 ). In human, IGF1R is located on the long arm of chromosome 15, and 36 different probable mutations have been reported ( 34 ).…”
Section: Effects Of Igf-1 On Organsmentioning
confidence: 99%
“…However, the gene expression of IGF-1 in prostate tissue was significantly increased (P = 0.001) and the expression of IGFBP3 was significantly decreased (P = 0.003) in patients with larger prostate size (>30 mL) ( 43 ). Local IGF-1 was reportedly upregulated in hyperplastic prostate tissues ( 33 ). Patients with acromegaly characterized by GH hypersecretion display high IGF-1 levels, and acromegaly patients are highly susceptible to IGF-1 related diseases including diabetes mellitus and BPH, suggesting IGF-1 regulation of various diseases.…”
Section: Cancers and Igf-1 Signalingmentioning
confidence: 99%